How IT changes careers: the role of career anchors and career identity - Algahtani, Matab (Auckland University of Technology, 2016)
Information technology (IT) has impacted almost every aspect of business and industry including employees and their career paths. Although it is evident that information technology has had a profound impact on the individual worker?from automation in the workplace and the changing nature of job tasks and roles?a concerted effort to understand how IT changes careers for the individual worker has not uniformly been addressed in the literature. In an effort to fill this gap and to better understand how information has impacted outcomes for the individual worker and his or her career, the current investigation utilized a meta-narrative approach to systematically review and analyse the literature. The results of this process revealed a total of 48 articles of relevance to the topics of career anchors and career identity. Pertinent themes identified suggest that career outcomes as they relate to information technology are directly impacted by personal characteristics of the worker as well as job satisfaction. Subsequently job satisfaction and satisfaction for information technology are shaped by variables such as IT training provided to workers and participation of workers in technology implementation. These results have implications for ensuring that organizations are able to meet the needs of workers to ensure that career development is successful in the wake of the introduction of IT.
Keywords: Changes to career trajectories; IT changes careers; Influences of Information Technology; Career anchors; Career identity; Information Technology on work